FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2012-2014 - Noor Rahmat Agus Putranto, 13.05.52.0131; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of asset growth, firm size, profitability, asset structure, firm age, cash holding, and liquidity on capital structure. This study uses data of property & real estate companies listed in Indonesia Stock Exchange (IDX). The sampling method in this research used purposive sampling with the observation period from 2012 to 2014. The data is processed as many as 111 companies. The relationship and (or) influence between variables are explained by using multiple regression analysis method. The results showed that firm size and firm age had a positive effect on capital structure; asset structure and liquidity had a negative effect on capital structure; asset grwoth, profitability and cash holding had no effect on capital structure.Keywords: Asset Growth, Firm Size, Profitability, Asset Structure, Firm Age, Cash Holding, Liquidity and Capital Structure